Regularity of Clinical Visits and Medication Adherence of Patients with Hypertension or Diabetes in Rural Yunnan Province of China - Gao, Qiufeng; Peng, Lanxi; Min, Wenbin; Nie, Jingchun; Aiqin Wang; Yaojiang Shi; Shi, Haonan; Teuwen, Dirk E.; Hongmei Yi (International Journal of Environmental Research and Public Health, 2020)
Chronic diseases can be controlled through effective self-management. The purpose of this study is to explore the regularity of clinical visits and medication adherence of patients with hypertension or diabetes (PWHD), and its association with the first experience with care and individual factors in rural Southwestern China. This cross-sectional study was carried out in Yunnan province in 2018 and recruited 292 PWHD and 122 village clinics from 122 villages in 10 counties. Participants were interviewed using a structured questionnaire. Results show around 39% of hypertensive and 25% of diabetic patients neither visited physicians nor took medicine regularly during the preceding three months of the interview date. The regression results further indicated that individual characteristics of the PWHD, including patient age, health status, and economic level, as well as their first experience with care, were significantly associated with their regular healthcare behavior. In addition to providing medical services, on average each sample village clinic, with around two physicians, simultaneously managed 180 hypertensive and 45 diabetic patients. This study revealed the need for further reforms in terms of improving self-management and thus recommends an increase in the quantity and the quality of human resources in the primary healthcare realm in rural China.
Keywords: Chronic Disease; diabetes; Hypertension; Index Medicus; Rural China; self-management